A NIR-II-emitting gold nanocluster-based drug delivery system for smartphone-triggered photodynamic theranostics with rapid body clearance. (December 2021) - Kong, Yifei; Santos-Carballal, David; Martin, David; Sergeeva, Natalia N.; Wang, Weili; Liu, Guishi; Johnson, Benjamin; Bhayana, Brijesh; Lin, Zuantao; Wang, Yensheng; Le Guével, Xavier; de Leeuw, Nora H.; et al.
Graphical abstract: Abstract: Nanomedicine has grown structurally complex in order to perform multiple tasks at a time. However, their unsatisfied reliability, uniformity and reproducibility account for the high rates of attrition in translational research. So far, most studies have been one-sidedly focused on the treatment efficacy of inorganic nanoparticles as cancer therapeutics, but overlook their elimination from the body – a key factor in getting regulatory approval. Instead of developing a new drug nanocarrier with uncertain future in medical practice, we therefore choose to leverage the utility of promising and translatable gold nanoclusters (AuNCs) for designing a simple but robust "all-in-one" nanocluster drug delivery system, where the AuNCs not only strengthen the renal clearance of neutral red (NR) as a model drug, but also aid its passive tumor targeting via the enhanced permeability and retention (EPR) effect. More interestingly, NR can stimulate the production of reactive oxygen species (ROS) to suppress tumor growth under ultralow-level radiation with a smartphone's torch (fluence rate: 8 mW/cm 2 ). This finding is especially valuable to low- and middle-income countries lacking resources in healthcare settings. By means of first-principles simulations, we also study in-depth the energies, structural and electronic properties of the AuNCs emitting in the second near-infrared window (NIR-II, 1000–1700 nm). In brief, our model fulfills safety, effectiveness and cost-effectiveness requirements for translational development.